" The Effect Of Teaching Using (Presseisen) A Model On The Achievement Of The Third Intermediate Grade Students In Chemistry" (Journal of the College of Basic Education, 2026)
The research seeks to understand "The effect of teaching using (presseisen) a model on the achievement of the third intermediate grade students in chemistry" . The study populaation was limited to third year intermediate students in secondary and intermediate schools associated with the General Directorate of Education of Ninava Governorate / Talkaif for the academic year ( 2025/2026).The researchers adopted a quasi-a partially controlled experimental design control, which required two independent groups: an experimental group taught using the (presseisen) model and a control group taught through the conventional method, followed by a post-test. The study sample was selected purposively from (Deir Umm Tutha Secondary) School for Boys and consisted of (49) Students were distributed between two . The experimental group included (25) students, while the control group consisted of (24) students.In light of the reviewed instructional topics and the general objectives, the researchers formulated 203 behavioral objectives based on Bloom’s taxonomy across its six cognitive levels. They proceeded to develop an achievement test as the research instrument. In its final form, the test contained (40) Multiple-choice questions, each consisting of four options Following statistical analysis using the t-test for two independent samples and processing the data with (SPSS and Excel). the outcomes indicated that students in the experimental group who studied chemistry according to the (presseisen) model outperformed those in the control group who were taught the same Students taught using the traditional method on the achievement test.